Laporan Kasus: Manajemen Perawatan Gigi pada Pasien dengan Periodontitis Kronis disertai Diabetes Mellitus - Agus Surachman; Marsaa Paramita; Aris Aji Kurniawan (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2019)
Diabetes mellitus is a metabolic disease in which blood sugar levels are abnormally because the body does not produce enough insulin (type 1) and insulin deficiency (type II). The condition of diabetes can worsen the periodontal tissue. Purpose of this case report is to explain the characteristics, oral manifestations and dental management of patients with diabetes. A 53-year-old request to made aartificial denture. Intraoral examination presented loss of teeth 35, 36, 37, 46, 47 and dental roots 23, 24, 27, 38, 48. Patients have a history of diabetes with Metformin 500 mg oral therapy and have consumed it since 2016. The treatment plan is education, plaque control with supragingival scaling then extraction of the roots dental and making of removable partial dentures. Based on the results of lab tests showed blood glucose levels in October 177 mg / dl. Patients were instructed to maintain oral hygiene with mouthwash prescriptions and to continue diabetes treatment. Dental care in patients with diabetes must consider various things such as the patient's condition, stress reduction, dietary modifications, prophylactic medications, and routine monitoring of blood glucose levels